A walk in the night with Zhuangzi : musings on an ancient Chinese manuscript - Huang, Kuan-yun, 1978- (SUNY series in Chinese philosophy and culture., 2023)
"A complete translation and analysis of "All Things Flow into Form" (Fan wu liu xing), a recently discovered manuscript from the Warring States period (481-221 BCE)"--